Lean Approach to Quality Control Laboratory of Pharmaceuticals - Chowdhury, Nusrat (International Journal of Pharmaceutical and Life Sciences, 2012)
DOI: http://dx.doi.org/10.3329/ijpls.v1i1.12948 International Journal of Pharmaceutical and Life Sciences Vol.1(1) 2012